EFFECTIVENESS OF COOPERATIVE LEARNING MODEL OF PAIR CHECK TYPE AND THINK PAIR SHARE TYPE ON MATHEMATICAL LEARNING OUTCOMES OF CLASS VII STUDENTS OF SMP MUHAMMADIYAH 2 GAMPING YOGYAKARTA - Tsalits Al Jamilatun Layl; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Learning with discussion among friends in one table has been less effective. This condition makes the lowness of learning mathematics outcome. This research aims to determine whether there are differences outcome or not between using cooperative learning Pair Check (PC) type and using cooperative learning Think Pair Share (TPS) and comparing the effectiveness of cooperative learning Pair Check type and  Think Pair Share to the learning mathematics outcomes in class VII in second semester SMP Muhammadiyah 2 Gamping 2015/2016. The population in this research there are three class. Sampling takes two classes with a random sampling technique to the class. Collecting the data is done by the test method. Before analyzing the data, it takes the prerequisite test with contain normality test and homogeneity test. For testing the hypothesis of this research, it uses one side t-test with a significant level of 5%. The results of this research on a significant level of 5% and dk=72 show that there are differences in learning mathematics outcomes of the students who use cooperative learning model PC type and TPS type. It is shown by the value  and  which means  cooperative learning model PC type is more effective than the cooperative learning model TPS type to the learning mathematics outcomes of the students.  It is shown by the value of  and  which means.